Development of a Community Health and Behavior Modifying System for Family’s Care Giver with Health Network Center, Bangpakong Districts - ซุ่นฮะ, เตือนใจ; จาดเงิน, กนกศรี (Princess of Naradhiwas University Journal, 2019)
This research and development study aimed to develop a health behavior modifying program for family caregivers with the cooperation of a community health network in central Thailand. The study comprised 3 stages: 1) situation analysis and need assessment, 2) designing and developing a program, and 3) evaluation the program. Sample were 15 caregivers who took care of at least 1 person in a family with a non-communicable disease, such as overweight or potbelly or obesity. Pre-test and post-test were conducted. Research instruments were: 1) the learning achievement Kuder Richardson 20 test (KR-20) with a score of 0.87, 2) the Health literacy measurement with reliability of 0.75., and 3) a questionnaire to assess satisfaction towards the developed system (IOC=1.00). Statistics employed in the research were frequency, percentage, mean, standard deviation, independent t-test, and paired t-test. Research findings indicated that most of participants (92.7%) rated the highest need in terms of finding ways to modify health behaviors that were appropriate for themselves. The developed health behavior modifying system for family caregivers with participation of community health network consisted of the 6 components including; 1) objectives, 2) target group, 3) contents, 4) media, 5) training activities, and 6) evaluation. The developed system was approved by the experts as being feasible for implementation, with the Index of Item Objective Congruence (IOC), yielding a value of 0.92. The post-learning achievement of the participants was significantly higher than their pre-learning achievement (p<.05). Most of participants had proper health behaviors at 80% and above. And they were satisfied with the developed program at the highest level